KEPENTINGAN INDONESIA MENGEKSPOR IKAN TUNA KE AMERIKA SERIKAT TAHUN 2012-2015 - Alfajri, Said Irsyam; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to explain the interests of Indonesia Exporting Tuna Fish to United States in 2012-2015. The United States is one of the main destinations for the export of fishery products from Indonesia. Indonesia has the natural potential resources in the international market. The United States should meet the huge market demand for tuna while the US seas alone produce less tuna and must import from other countriesThe data of this research was obtained from books, journals, articles, official documents and websites that support the hypothesis. The author used Librealism, the theories used in this research consist of National Interest, and level analyze is a national state.The method that used in this research is the method descriptive explanation which explain the problem and the situation with the fact in the field.The results of this study indicate that the export of tuna from Indonesia to the United States provides the benefits of both countries. Since this export of tuna to United States begun, this export activity has contributed to the economy of the fisherman and the Indonesian economy. Indonesia with oceans and abundant marine products are required to harness its seafood well.Key Words : National Interest, International Relations, Indonesia, United States, Export